Measuring Activated Clotting Time during Cardiac Catheterization and PCI: The Effect of the Sampling Site. (13th September 2021) - Heemelaar, J. C; Berkhout, T.; Heestermans, A. A. C. M.; Zant, J. C.; de Vos, A. M. J.; Verouden, N. J. W.; Dirksen, M. T.; van Ramshorst, J.
Abstract : Background/Purpose . We aimed to investigate the influence of the sampling site on the variability of ACT measurement. Activated clotting time (ACT) has been used for decades in cardiac surgery and interventional cardiology to assess unfractionated heparin activity. However, standardized protocols for the use of ACT measurement in the catheterization laboratory are lacking. Methods/Materials . After elective cardiac catheterization, ACT measurements were collected in simultaneously obtained blood samples from three different sample sites: the arterial catheter, arterial sheath, and peripheral intravenous line. Measurements were performed using the i-Stat® device (Abbott, Princeton, NJ, USA). The study was conducted with approval of the local medical ethical committee. Results . In 100 patients (mean age 67.1, 65% male), no significant differences were observed in ACT values obtained from the guiding catheter and arterial sheath (mean difference (MD) −18.3 s; standard deviation (SD) 96 s; P = 0.067 ). Contrarily, ACT values obtained from the intravenous line were significantly lower as compared to values obtained from the guiding catheter (MD 25.7 s; SD 75.5; P = 0.003 ) and arterial sheath (MD 39 s; SD 102.8; P < 0.001 ). Furthermore, ACT measurements from the arterial sheath showed a statistically significant proportional bias when compared to the other sampling sites (sheath vs. catheter, r  = 0.761, P = 0.001 ; sheath vs. IVL, r  = 1.013, P < 0.001 ). Conclusions . The present study shows statistical significance and possibly clinically relevant variations between ACT measurements from different sample sites. Bias in ACT measurements may be minimized by using uniform protocols for ACT measurement during cardiac catheterization.